Analysis of Potentially Inappropriate Prescriptions (PIP) Based on STOPP/START Criteria in Geriatric Patients with Cardiovascular Disorders at Hasan Sadikin Hospital, Bandung, West Java, Indonesia - Fathurrahmi, Fathurrahmi; Wilar, Gofarana; Levita, Jutti; Winarni, Rina (Pharmacology and Clinical Pharmacy Research, 2023)
The geriatric population in Indonesia is increasing rapidly every year. The large number of drugs consumed by geriatric patients results in potentially inappropriate prescriptions (PIP) in the form of mis-prescribing drugs (potentially inappropriate medicines or PIM) and under-prescribing drugs (potentially prescription omission or PPO). In Indonesia, especially in Bandung, there is limited research on PIP in geriatric patients with cardiovascular disorders (CVDs). This study aims to identify PIP and factors that influence PIM and PPO based on STOPP/START criteria and the relationship between the incidence of PIM and kidney function in geriatric inpatients with CVDs at Hasan Sadikin Hospital, Bandung, West Java, Indonesia. The present retrospective study was cross-sectionally conducted from January to December 2022. The Chi-square tests were carried out to determine factors that were significantly related to PIM and PPO. Of the 192 patients, 33.4% patients experienced PIM with the most being NSAIDs with eGFR <30 mL/min/1.73 m2 (36%). As many as 35% of patients experienced PPO with the most frequent PPO not being given angiotensin-converting enzyme inhibitor (ACEi) in patients with systolic heart failure (41.8%). Factors that were significantly associated with PIM were comorbid kidney dysfunctions (OR 5; 95% CI: 2.367-10.342), and no factors were found that were significantly associated with PPO. Taking everything into consideration, it was found that PIM and PPO were common in hospitalized geriatric patients with CVDs. Kidney dysfunctions are a risk factor for PIM. These findings suggest that it is important to evaluate prescribing for geriatric patients during hospitalization using STOPP/START criteria to reduce the prevalence of PIP